"Pollution Pods": The merging of art and psychology to engage the public in climate change. (November 2019) - Sommer, Laura Kim; Swim, Janet Kay; Keller, Anna; Klöckner, Christian Andreas
Highlights: Environmental art and psychology identify mechanisms of creating engagement for climate change. Exposure to emmersiv activism art increased intentions to engage in actions to address pollution and climate change. Sadness, helplessness and anger were strongest emotions impacting intentions to act. Ascription of responsibility was strongest cognition impacting intentions to act. Abstract: Environmental artists have risen to the challenge of communicating the urgency of public action to address environmental problems such as air pollution and climate change. Joining this challenge, the immersive artwork Pollution Pods (PPs) was created through a synthesis of knowledge from the fields of environmental psychology, empirical aesthetics, and activist art. This study summarizes the scientific process in this transdisciplinary project and reports the findings from a questionnaire study ( N  = 2662) evaluating the effect of the PPs on visitors. Data were collected at the first two exhibitions of the installation, one in a public park in Trondheim, Norway, and one at Somerset House, London, UK. Intentions to act were strong and slightly increased after visiting the art installation. Individual changes in intentions were positively associated with self-reported emotions of sadness, helplessness, and anger and self-reported cognitive assessment their awareness of the environmental consequences of their action, their willingness to take responsibility for their consequences, and belief in the relevance of environmental problems for daily life. Education and age were negatively associated with intentions. Despite favorable intentions, however, taking advantage of an actual behavioral opportunity to track one's climate change emissions behavior after visiting the PPs could not be detected. We conclude that environmental art can be useful for environmental communication and give recommendations for communicators on how to best make use of it. We emphasize the potential benefits of art that encourages personal responsibility and the need for valid behavior measures in environmental psychological research.